RESTRUKTURISASI PERUSAHAAN DALAM KONTEKS AKUISISI: IMPLIKASI HUKUM DAN STRATEGI BISNIS DI INDONESIA - Fransisca Andriani, Yosephine; Risca Selfeny (Jurnal Hukum Statuta, 2024)
This article discusses corporate restructuring in the context of acquisitions, focusing on the legal implications and business strategies in Indonesia. The research begins by examining the legal and regulatory framework governing acquisitions, including their compatibility with corporate law. Next, the study discusses the factors driving companies to use acquisitions as a strategic tool for expansion, such as market competition, financial pressures, and globalization. The study analyzes best practices in the legal and business fields, demonstrating their role in ensuring a smooth acquisition process. The urgency of this study lies in understanding the challenges in mergers and acquisitions (M&A), which involve not only financial and operational issues but also legal disputes and compliance with mandatory laws in Indonesia. Using a qualitative approach, supported by case analysis and literature review, this article identifies important factors that affect the success or failure of acquisitions, such as due diligence, valuation accuracy, and cultural integration. The results show that while acquisitions offer great opportunities for corporate growth and market penetration, they also carry risks if they are not aligned with regulatory standards and strategic objectives. The study provides key recommendations for stakeholders, including improved corporate governance and in-depth legal assessments prior to acquisitions. The conclusion emphasizes that a well-structured acquisition process can support corporate sustainability and long-term economic growth, provided that all legal and strategic aspects are carefully managed.